"Click handle"-modified 2′-deoxy-2′-fluoroarabino nucleic acid as a synthetic genetic polymer capable of post-polymerization functionalization. Issue 23 (25th May 2022) - Wu, Kevin B.; Skrodzki, Christopher J. A.; Su, Qiwen; Lin, Jennifer; Niu, Jia
Abstract : Polymerase-mediated incorporation of a "click handle"-modified fluoroarabinonucleic acid (cmFANA) triphosphate produces a new class of nuclease-resistant, evolvable genetic polymers that can be functionalized with azide-containing molecules. Abstract : The functions of natural nucleic acids such as DNA and RNA have transcended genetic information carriers and now encompass affinity reagents, molecular catalysts, nanostructures, data storage, and many others. However, the vulnerability of natural nucleic acids to nuclease degradation and the lack of chemical functionality have imposed a significant constraint on their ever-expanding applications. Herein, we report the synthesis and polymerase recognition of a 5-(octa-1, 7-diynyl)uracil 2′-deoxy-2′-fluoroarabinonucleic acid (FANA) triphosphate. The DNA-templated, polymerase-mediated primer extension using this "click handle"-modified FANA (cmFANA) triphosphate and other FANA nucleotide triphosphates consisting of canonical nucleobases efficiently generated full-length products. The resulting cmFANA polymers exhibited excellent nuclease resistance and the ability to undergo efficient click conjugation with azide-functionalized molecules, thereby becoming a promising platform for serving as a programmable and evolvable synthetic genetic polymer capable of post-polymerization functionalization.